‘Tragedy’ and Space of Commemoration: An Inquiry to Semanggi Tragedy’s Significance on Jakarta’s Urban Space - Feby Hendola (Department of Architecture Universitas Muhammadiyah Jakarta, 2018)
A City does not only exist with its physical feature but also with its intangible thing within it, including the people’s memory. Our memory, either it is delightful or unpleasant, plays role on molding our perception about our environment. Meanwhile we also tend to build something—to construct our environment—for commemorating significant events. Regarding this phenomenon, this paper aimed to understand how a tragic event affects urban space by examining conceptions of “tragedy” and “absential feature” and their relation to space of commemoration. As a reflection of the conceptual inquiry, this paper analyzed how Semanggi Tragedy, which had happened on 1998-1999, affected Jakarta’s urban space. The study showed that the tragedy brought ‘absence’ that urges people to create tangible feature to response their grief, loss and hopes. Semanggi’s physical development—as a way to move on—only emphasizes the ‘absence’ of the tragedy and does not stop people to not forget it.